In Good Faith : Canadian Churches Against Apartheid. - Pratt, Renate (Wilfrid Laurier University Press, 2006)
In retrospect it is difficult to accept that Western democracies have implicitly supported, or at least tolerated, the legalized system of white supremacy in South Africa known as apartheid. Renate Pratt's new book, In Good Faith, explains why the Christian churches were among the first to publicly protest, and why they provided such cogent and determined international support for the struggle against apartheid. The Taskforce on the Churches and Corporate Responsibility is a coalition of Christian churches that for nearly twenty years was one of Canada's leading anti-apartheid advocates. As the first co-ordinator of this Taskforce, Renate Pratt was at the centre of the early anti-apartheid initiatives in Canada and consequently is able to supply a clear and accurate view. The book traces the history of exchanges between the Taskforce and successive ministers and senior civil servants of the Department of External Affairs. It details the reluctant and weak responses offered by the Canadian government and business community right up to the time of Nelson Mandela's release from prison. In Good Faith will be of particular interest to Canadian Christians concerned with ecumenical co-operation and with the social and political dimensions of their faith. Equally, it will appeal to those interested in the impact of public interest organizations on public policy or the relationship between politics and business interests.
10. Final ReflectionsSelected Bibliography; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z.
Print version record.
eBooks on EBSCOhost
Keywords: Taskforce on the Churches and Corporate Responsibility; Taskforce on the Churches and Corporate Responsibility; Race relations -- Religious aspects -- Christianity; Apartheid -- South Africa; Church and industry -- Canada; Christianity and politics -- Canada; Relations raciales -- Aspect religieux -- Christianisme; Apartheid -- Afrique du Sud; Église et industrie -- Canada; Christianisme et politique -- Canada; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Apartheid; Christianity and politics; Church and industry; Race relations -- Religious aspects -- Christianity; Canada; South Africa; Electronic books